Compound for treating fluorine-containing wastewater and preparation method thereof
By combining silanized calcite coated by ferroalloy with hydrogel polymer, silanized calcite particles coated by porous hydrogel-ferroalloy is formed, which solves the problems of high cost of fluorine-containing wastewater treatment and unstable effect in the prior art, and achieves efficient removal of fluorine ions.
Patent Information
- Application Number
- CN202411640706.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
When treating fluorine-containing wastewater, the prior art has problems such as high cost, unstable treatment effect and large amounts of difficult waste residue when treating fluorine-containing wastewater, and urgently needs a low-cost and good-effect material for fluorine-containing wastewater treatment.
Using a composite, silanized calcite coated by ferroalloy and hydrogel polymer is combined to form porous hydrogel-ferroalloy-coated silanized calcite particles, and finally etched in hydrofluoric acid to form a porous structure to improve adsorption.
It realizes effective removal of fluorine ions in fluorine-containing wastewater, has a porous structure and high adsorption properties, and the surface contains a large amount of positive charge, which can effectively adsorb and covalently bind anion ions.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sewage treatment, and in particular, relates to a composite material for treating fluorine-containing wastewater and a preparation method thereof. Background Art
[0002] Fluorine in its combined state is widely used in the synthesis of chemical materials, the manufacture of semiconductor components (such as silicon chips), aluminum smelting and aluminum alloy surface treatment, steel processing, metal smelting, etc. If the fluoride-containing wastewater generated during the application process is not properly treated, it will not only harm the ecological environment, but also cause serious harm to human health, such as dental fluorosis and fluorosis, and can also cause damage to most organs, nervous system and cell membranes in the body.
[0003] At present, common fluoride-containing wastewater treatment mainly includes coagulation and sedimentation, adsorption filtration, membrane separation, chemical precipitation, etc. The coagulation and sedimentation method is to add coagulants and flocculants to the wastewater after pH adjustment, and then react with the fluoride ions in the wastewater to form complexation, sweeping, adsorption and other effects, so as to generate large flocculent precipitates and settle out of the wastewater. The coagulation and sedimentation process is mature, simple to operate, and requires little investment, which is suitable for the treatment of large-scale fluoride-containing wastewater. However, the addition of large doses of coagulants will produce a large amount of waste residue that is difficult to treat, increasing the treatment cost. As a common method for treating fluoride-containing wastewater, the adsorption filtration method utilizes the pore structure and huge specific surface area of the adsorbent to diffuse the fluoride in the wastewater on the surface of the adsorbent and bind on the surface, or relies on the weak intermolecular force between the surface of the adsorbent and the fluoride ions in the wastewater to achieve adsorption and capture of fluoride ions, and realize solid-liquid separation to remove fluoride ions from the wastewater. This process is simple to operate and has a relatively stable effect in removing fluoride, and can be recycled by regeneration to achieve recycling. However, the adsorption capacity of common adsorbents is not high, and they also have the harsh limitation of high cost, which makes it impossible to become the mainstream defluorination process. Membrane separation methods include reverse osmosis, nanofiltration and other methods. Reverse osmosis and electrodialysis are commonly used to treat fluoride-containing water. Reverse osmosis uses the principle of osmotic pressure difference of the solution to intercept fluoride ions through the selective permeability of the semipermeable membrane and allow water molecules to pass through for defluorination. This method is simple to operate, takes up little space, removes fluoride thoroughly, and is technologically advanced. However, the reverse osmosis method has extremely high requirements for the quality of inlet and outlet water, requires pretreatment, and the price of the semipermeable membrane is high, which increases the treatment cost and makes it impossible to promote it on a large scale. Electrodialysis is a process of separating charged ions driven by electric field. Under the action of different electric field gradients, ions are separated by directional migration through ion exchange membranes. As a simple environmental protection technology, electrodialysis has many advantages such as no addition of any chemical reagents, no generation of harmful solids, and no material conversion. However, the heat generated by electrodialysis technology in actual applications may cause expansion of exchange membranes and gaskets, leakage, and expensive electrode materials. The chemical precipitation process is to add a certain precipitant, such as calcium salt, aluminum salt and magnesium salt, to the fluoride-containing wastewater, and use the precipitant to react chemically with the fluoride ions in the wastewater to generate a precipitate that is insoluble in water. Through natural sedimentation, the pollutants are separated from the water solid and liquid to achieve the effect of removing fluoride pollutants. At present, the chemical precipitation method is widely used in the treatment of fluoride-containing wastewater. It has been greatly promoted due to its good treatment effect, low cost and simple operation. However, this process also has the disadvantages of slow sedimentation and unstable fluoride concentration in the effluent.
[0004] Therefore, there is an urgent need for a low-cost, high-effect material for the treatment of fluoride-containing wastewater. Summary of the invention
[0005] The primary purpose of the present invention is to provide a composite for treating fluorine-containing wastewater and a preparation method thereof, so as to achieve effective treatment of fluorine-containing wastewater.
[0006] To this end, the present invention provides the following technical solutions.
[0007] One aspect of the present invention provides a method for preparing a composite for treating fluorine-containing wastewater, the method comprising the following steps:
[0008] Liquid aluminum-iron alloy and silanized calcite are added to anhydrous ethanol in a mass ratio of 1:0.1-0.3 and subjected to ultrasonic treatment in an ice-water bath, followed by suction filtration, and the obtained solid product is washed and dried to obtain aluminum-iron alloy-coated silanized calcite;
[0009] Polyethylene glycol diacrylate, cationic monomer and nonionic monomer are dissolved in water in a mass ratio of 1:1-3:1-3:20-50 to obtain a hydrogel solution; silanized calcite coated with aluminum-iron alloy is added to the obtained hydrogel solution, and then an initiator is added to stir and react at 30-100° C. for 30-60 minutes, and then a cross-linking agent is added to continue stirring and reacting for 1-3 hours, and after the reaction is completed, the reaction is allowed to stand for 40-60 minutes, and finally the obtained product is washed, dried and granulated to obtain hydrogel-silanized calcite particles coated with aluminum-iron alloy with a particle size of 1-5 mm;
[0010] The obtained hydrogel-aluminum-iron alloy-coated silanized calcite particles are placed in a 1-5% hydrofluoric acid solution and soaked for 10-30 minutes. Finally, the product is taken out, washed and dried to obtain a final product.
[0011] In a preferred embodiment of the present invention, the iron content in the aluminum-iron alloy is 10-30%, and the rest is aluminum and inevitable impurities, and the impurity content is not higher than 0.01%.
[0012] In a preferred embodiment of the present invention, the silanized calcite is prepared according to the following method: washing and drying the calcite, grinding it and passing it through a 80-100 mesh sieve to obtain calcite powder;
[0013] The obtained calcite powder is placed in a silane coupling agent and ultrasonically treated at a power of 600 to 800 W for 30 to 50 minutes, then allowed to stand for 10 to 30 minutes, and then filtered, and the obtained precipitate is dried to obtain silanized calcite.
[0014] In a preferred embodiment of the present invention, the silane coupling agent is selected from any one of vinyl triethoxy silane, vinyl trimethoxy silane and vinyl tri (β-methoxyethoxy) silane.
[0015] In a preferred embodiment of the present invention, the ultrasonic treatment conditions are: power 300-600W, time 10-20min, and the working process is 10s ultrasonication followed by 1s pause.
[0016] In a preferred embodiment of the present invention, the cationic monomer is selected from at least one of diallyldimethylammonium chloride, acrylamidopropyltrimethylammonium chloride, methacrylamidopropyltrimethylammonium chloride, acryloyloxyethyltrimethylammonium chloride, methacryloyloxyethyltrimethylammonium chloride, and acryloyloxyethyltrimethylammonium chloride.
[0017] In a preferred embodiment of the present invention, the nonionic monomer is selected from at least one of acrylamide, dimethylacrylamide, diethylacrylamide, hydroxyethylacrylamide, dimethylaminopropylacrylamide and dimethylaminopropylmethacrylamide.
[0018] In a preferred embodiment of the present invention, the added amount of the aluminum-iron alloy-coated silanized calcite is 0.3-0.7 of the mass of polyethylene glycol diacrylate.
[0019] In a preferred embodiment of the present invention, the initiator is selected from any one of potassium persulfate, ammonium persulfate and sodium persulfate.
[0020] In a preferred embodiment of the present invention, the amount of the initiator added is 0.2% to 0.5% of the mass of the cationic monomer.
[0021] In a preferred embodiment of the present invention, the cross-linking agent is selected from any one of catechol, hydroquinone and resorcinol.
[0022] In a preferred embodiment of the present invention, the amount of the cross-linking agent added is 0.1-0.3% of the mass of the cationic monomer.
[0023] By means of the above technical solution, the present invention has at least the following advantages:
[0024] The material obtained by the present invention is a porous hydrogel-aluminum-iron alloy-coated silanized calcite particle composite, wherein calcite plays the role of a carrier / skeleton, is coated by an aluminum-iron alloy to obtain an aluminum-iron alloy-coated silanized calcite, and then the obtained aluminum-iron alloy-coated silanized calcite is used as the core, a hydrogel polymer is used for shell wrapping, and granulation is performed to obtain hydrogel-aluminum-iron alloy-coated silanized calcite composite particles, and finally etching is performed by hydrofluoric acid to obtain porous hydrogel-aluminum-iron alloy-coated silanized calcite composite particles. The composite not only has a porous structure to give it adsorption, but also contains a large amount of positive charges on the surface, which can effectively adsorb and covalently bind anionic ions. After experimental verification, the composite obtained by the present invention can achieve effective removal of fluoride ions in wastewater.
[0025] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0026] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Unless otherwise specified, the percentage content involved in the present invention refers to mass percentage for solid-liquid mixing and solid-solid mixing, and refers to volume percentage for liquid-liquid mixing.
[0028] Unless otherwise specified, the percentage concentrations referred to in the present invention all refer to final concentrations, which refer to the percentage of the added component in the system after the addition of the component.
[0029] The temperature parameters in the present invention, if not specifically limited, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument.
[0030] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0031] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0032] Embodiment 1:
[0033] A method for preparing a composite for treating fluorine-containing wastewater comprises the following steps:
[0034] The calcite was washed, dried, ground and passed through an 80-mesh sieve to obtain calcite powder; the obtained calcite powder was placed in vinyltriethoxysilane and ultrasonically treated at a power of 700 W for 40 minutes, then allowed to stand for 20 minutes, and then filtered, and the obtained precipitate was dried to obtain silanized calcite.
[0035] Liquid aluminum-iron alloy (iron content is 20%, the rest is aluminum and inevitable impurities) and silanized calcite are added to anhydrous ethanol in a mass ratio of 1:0.2 and subjected to ice-water bath ultrasonic treatment at 450 W for 15 min, wherein the ultrasonic treatment is paused for 1 second after every 10 seconds, and then filtered, and the obtained solid product is washed and dried to obtain aluminum-iron alloy-coated silanized calcite.
[0036] Polyethylene glycol diacrylate, diallyl dimethyl ammonium chloride and acrylamide were dissolved in water in a mass ratio of 1:2:2:35 to obtain a hydrogel solution. The obtained hydrogel solution was added with aluminum-iron alloy-coated silanized calcite (the amount added was 0.5 of the mass of polyethylene glycol diacrylate), and then ammonium persulfate (the amount added was 0.35% of the mass of diallyl dimethyl ammonium chloride) was added and stirred at 80°C for 45 minutes, and then catechol (the amount added was 0.2% of the mass of diallyl dimethyl ammonium chloride) was added and stirred for 2 hours. After the reaction was completed, the mixture was allowed to stand for 50 minutes, and finally the obtained product was washed, dried and granulated to obtain hydrogel-aluminum-iron alloy-coated silanized calcite particles with a particle size of 3 mm.
[0037] The obtained hydrogel-aluminum-iron alloy-coated silanized calcite particles are immersed in a 3% hydrofluoric acid solution for 20 minutes, and finally the product is taken out, washed and dried to obtain a final product.
[0038] Embodiment 2:
[0039] A method for preparing a composite for treating fluorine-containing wastewater comprises the following steps:
[0040] The calcite was washed, dried, ground and passed through an 80-mesh sieve to obtain calcite powder; the obtained calcite powder was placed in vinyltrimethoxysilane and ultrasonically treated at a power of 600 W for 50 minutes, then allowed to stand for 10 minutes, and then filtered, and the obtained precipitate was dried to obtain silanized calcite.
[0041] Liquid aluminum-iron alloy (iron content is 10%, the rest is aluminum and inevitable impurities) and silanized calcite are added to anhydrous ethanol in a mass ratio of 1:0.3 and subjected to ice-water bath ultrasonic treatment at 600 W for 10 min, wherein there is a 1-s pause for every 10 s of ultrasonic treatment. The solid product is then filtered, washed and dried to obtain aluminum-iron alloy-coated silanized calcite.
[0042] Polyethylene glycol diacrylate, acrylamidopropyl trimethylammonium chloride and dimethylacrylamide were dissolved in water in a mass ratio of 1:3:1:50 to obtain a hydrogel solution. The obtained hydrogel solution was added with aluminum-iron alloy-coated silanized calcite (the amount added was 0.3 of the mass of polyethylene glycol diacrylate), and then ammonium persulfate (the amount added was 0.2% of the mass of acrylamidopropyl trimethylammonium chloride) was added and stirred at 80°C for 60 minutes, and then hydroquinone (the amount added was 0.1% of the mass of acrylamidopropyl trimethylammonium chloride) was added and stirred for 1 hour. After the reaction was completed, the mixture was allowed to stand for 60 minutes, and finally the obtained product was washed, dried and granulated to obtain hydrogel-aluminum-iron alloy-coated silanized calcite particles with a particle size of 3 mm.
[0043] The obtained hydrogel-aluminum-iron alloy-coated silanized calcite particles are immersed in a 1% hydrofluoric acid solution for 30 minutes, and finally the product is taken out, washed and dried to obtain a final product.
[0044] Embodiment 3:
[0045] A method for preparing a composite for treating fluorine-containing wastewater comprises the following steps:
[0046] The calcite was washed, dried, ground and passed through an 80-mesh sieve to obtain calcite powder; the obtained calcite powder was placed in vinyltri(β-methoxyethoxy)silane and ultrasonically treated at a power of 800 W for 30 minutes, then allowed to stand for 30 minutes, and then filtered, and the obtained precipitate was dried to obtain silanized calcite.
[0047] Liquid aluminum-iron alloy (iron content is 30%, the rest is aluminum and inevitable impurities) and silanized calcite are added to anhydrous ethanol in a mass ratio of 1:0.1 and subjected to ice-water bath ultrasonic treatment at 300 W for 20 min, wherein the ultrasonic treatment is paused for 1 second after every 10 seconds, and then filtered, and the obtained solid product is washed and dried to obtain aluminum-iron alloy-coated silanized calcite.
[0048] Polyethylene glycol diacrylate, methacrylamidopropyl trimethylammonium chloride and diethylacrylamide were dissolved in water in a mass ratio of 1:1:3:20 to obtain a hydrogel solution. The obtained hydrogel solution was added with aluminum-iron alloy-coated silanized calcite (the amount added was 0.7 of the mass of polyethylene glycol diacrylate), and then ammonium persulfate (the amount added was 0.5% of the mass of methacrylamidopropyl trimethylammonium chloride) was added and stirred at 80°C for 30 minutes, and then resorcinol (the amount added was 0.3% of the mass of methacrylamidopropyl trimethylammonium chloride) was added and stirred for 3 hours. After the reaction was completed, the mixture was allowed to stand for 40 minutes, and finally the obtained product was washed, dried and granulated to obtain hydrogel-aluminum-iron alloy-coated silanized calcite particles with a particle size of 3 mm.
[0049] The obtained hydrogel-aluminum-iron alloy-coated silanized calcite particles are placed in a 5% hydrofluoric acid solution and soaked for 10 minutes. Finally, the product is taken out, washed and dried to obtain a final product.
[0050] Comparative Example 1:
[0051] A method for preparing a composite for treating fluorine-containing wastewater comprises the following steps:
[0052] Polyethylene glycol diacrylate, diallyl dimethyl ammonium chloride and acrylamide were dissolved in water in a mass ratio of 1:2:2:35 to obtain a hydrogel solution. Aluminum-iron alloy (the amount added was 0.5 of the mass of polyethylene glycol diacrylate) was added to the obtained hydrogel solution, and then ammonium persulfate (the amount added was 0.35% of the mass of diallyl dimethyl ammonium chloride) was added and stirred at 80°C for 45 minutes, and then catechol (the amount added was 0.2% of the mass of diallyl dimethyl ammonium chloride) was added and stirred for 2 hours. After the reaction was completed, the mixture was allowed to stand for 50 minutes, and finally the obtained product was washed, dried and granulated to obtain hydrogel-aluminum-iron alloy particles with a particle size of 3 mm.
[0053] The obtained hydrogel-aluminum-iron alloy particles were placed in a 3% hydrofluoric acid solution and soaked for 20 minutes. Finally, the product was taken out, washed and dried to obtain the final product.
[0054] Comparative Example 2:
[0055] A method for preparing a composite for treating fluorine-containing wastewater comprises the following steps:
[0056] The calcite was washed, dried, ground and passed through an 80-mesh sieve to obtain calcite powder; the obtained calcite powder was placed in vinyltriethoxysilane and ultrasonically treated at a power of 700 W for 40 minutes, then allowed to stand for 20 minutes, and then filtered, and the obtained precipitate was dried to obtain silanized calcite.
[0057] Polyethylene glycol diacrylate, diallyl dimethyl ammonium chloride and acrylamide were dissolved in water in a mass ratio of 1:2:2:35 to obtain a hydrogel solution. Silylated calcite (the amount added was 0.5 of the mass of polyethylene glycol diacrylate) was added to the obtained hydrogel solution, and then ammonium persulfate (the amount added was 0.35% of the mass of diallyl dimethyl ammonium chloride) was added and stirred at 80°C for 45 minutes, and then catechol (the amount added was 0.2% of the mass of diallyl dimethyl ammonium chloride) was added and stirred for 2 hours. After the reaction was completed, the mixture was allowed to stand for 50 minutes, and finally the obtained product was washed, dried and granulated to obtain hydrogel-silanized calcite particles with a particle size of 3 mm.
[0058] The obtained hydrogel-silanized calcite particles were immersed in a 3% hydrofluoric acid solution for 20 minutes, and finally the product was taken out, washed and dried to obtain a final product.
[0059] Comparative Example 3:
[0060] A method for preparing a composite for treating fluorine-containing wastewater comprises the following steps:
[0061] Polyethylene glycol diacrylate, diallyl dimethyl ammonium chloride and acrylamide were dissolved in water in a mass ratio of 1:2:2:35 to obtain a hydrogel solution. Ammonium persulfate (the amount added was 0.35% of the mass of diallyl dimethyl ammonium chloride) was added to the obtained hydrogel solution and stirred for reaction at 80°C for 45 minutes, and then catechol (the amount added was 0.2% of the mass of diallyl dimethyl ammonium chloride) was added and stirred for reaction for 2 hours. After the reaction was completed, the mixture was allowed to stand for 50 minutes, and finally the obtained product was washed, dried and granulated to obtain hydrogel particles with a particle size of 3 mm.
[0062] The obtained hydrogel particles were placed in a 3% hydrofluoric acid solution and soaked for 20 minutes. Finally, the product was taken out, washed and dried to obtain the final product.
[0063] Comparative Example 4:
[0064] A method for preparing a composite for treating fluorine-containing wastewater comprises the following steps:
[0065] The calcite was washed, dried, ground and passed through an 80-mesh sieve to obtain calcite powder; the obtained calcite powder was placed in vinyltriethoxysilane and ultrasonically treated at a power of 700 W for 40 minutes, then allowed to stand for 20 minutes, and then filtered, and the obtained precipitate was dried to obtain silanized calcite.
[0066] Liquid aluminum-iron alloy (iron content is 20%, the rest is aluminum and inevitable impurities) and silanized calcite are added to anhydrous ethanol in a mass ratio of 1:0.2 and subjected to ice-water bath ultrasonic treatment at 450 W for 15 min, wherein the ultrasonic treatment is paused for 1 second after every 10 seconds, and then filtered, and the obtained solid product is washed and dried to obtain aluminum-iron alloy-coated silanized calcite.
[0067] The obtained aluminum-iron alloy-coated silanized calcite particles are placed in a 3% hydrofluoric acid solution and soaked for 20 minutes. Finally, the product is taken out, washed and dried to obtain a final product.
[0068] Comparative Example 5:
[0069] A method for preparing a composite for treating fluorine-containing wastewater comprises the following steps:
[0070] The calcite was washed, dried, ground and passed through an 80-mesh sieve to obtain calcite powder; the obtained calcite powder was placed in vinyltriethoxysilane and ultrasonically treated at a power of 700 W for 40 minutes, then allowed to stand for 20 minutes, and then filtered, and the obtained precipitate was dried to obtain silanized calcite.
[0071] Liquid aluminum-iron alloy (iron content is 20%, the rest is aluminum and inevitable impurities) and silanized calcite are added to anhydrous ethanol in a mass ratio of 1:0.2 and subjected to ice-water bath ultrasonic treatment at 450 W for 15 min, wherein the ultrasonic treatment is paused for 1 second after every 10 seconds, and then filtered, and the obtained solid product is washed and dried to obtain aluminum-iron alloy-coated silanized calcite.
[0072] Polyethylene glycol diacrylate, diallyl dimethyl ammonium chloride and acrylamide are dissolved in water in a mass ratio of 1:2:2:35 to obtain a hydrogel solution. The obtained hydrogel solution is added with aluminum-iron alloy-coated silanized calcite (the amount added is 0.5 of the mass of polyethylene glycol diacrylate), and then ammonium persulfate (the amount added is 0.35% of the mass of diallyl dimethyl ammonium chloride) is added and stirred at 80°C for 45 minutes, and then catechol (the amount added is 0.2% of the mass of diallyl dimethyl ammonium chloride) is added and stirred for 2 hours. After the reaction is completed, it is allowed to stand for 50 minutes. Finally, the obtained product is washed, dried and granulated to obtain hydrogel-aluminum-iron alloy-coated silanized calcite particles with a particle size of 3 mm, which is the final product.
[0073] Experiment: Testing the effect of different materials on the treatment of fluoride-containing wastewater
[0074] Experimental method: The water sample used in the test is fluorine-containing wastewater discharged by a chemical plant in Hebei. The fluoride ion concentration in the wastewater before treatment was 268.2 mg / L. The above wastewater was divided into 8 groups, each with 1L, numbered 1 to 8, and the composite materials of Examples 1 to 3 and Comparative Examples 1 to 5 were added respectively and stirred at a speed of 200rpm for 10min. The amount of added fluoride removal material was 1g per 1L of wastewater. After the stirring was completed, the fluoride ion content in the supernatant was detected after standing for 30min, and the fluoride removal rate was calculated;
[0075] Fluoride removal rate = (fluoride ion content before treatment - fluoride ion content after treatment) / fluoride ion content before treatment * 100%.
[0076] Experimental results: See Table 1.
[0077] Table 1 Statistics of fluorine removal rates of different fluorine removal materials
[0078] serial number Fluoride ion content after treatment (mg / L) Fluoride removal rate (%) 1 3.5 98.33% 2 4.2 98.07% 3 3.6 98.29% 4 36.9 85.92% 5 62.8 76.30% 6 116.7 56.28% 7 181.2 32.32% 8 95.4 64.19%
[0079] It can be seen from the results in Table 1 that, compared with Comparative Examples 1-5, the composites of Examples 1-3 of the present invention have an obvious removal effect on fluoride ions in fluoride-containing wastewater.
[0080] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite for treating fluorine-containing wastewater, characterized in that: The method comprises the following steps: Liquid aluminum-iron alloy and silanized calcite are added to anhydrous ethanol in a mass ratio of 1:0.1-0.3 and subjected to ultrasonic treatment in an ice-water bath, followed by suction filtration, and the obtained solid product is washed and dried to obtain aluminum-iron alloy-coated silanized calcite; Polyethylene glycol diacrylate, cationic monomer and nonionic monomer are dissolved in water in a mass ratio of 1:1-3:1-3:20-50 to obtain a hydrogel solution; silanized calcite coated with aluminum-iron alloy is added to the obtained hydrogel solution, and then an initiator is added to stir and react at 30-100° C. for 30-60 minutes, and then a cross-linking agent is added to continue stirring and reacting for 1-3 hours, and after the reaction is completed, the reaction is allowed to stand for 40-60 minutes, and finally the obtained product is washed, dried and granulated to obtain hydrogel-silanized calcite particles coated with aluminum-iron alloy with a particle size of 1-5 mm; The obtained hydrogel-aluminum-iron alloy-coated silanized calcite particles are placed in a 1-5% hydrofluoric acid solution and soaked for 10-30 minutes. Finally, the product is taken out, washed and dried to obtain a final product.
2. The preparation method according to claim 1, characterized in that: The iron content in the aluminum-iron alloy is 10-30%, and the rest is aluminum and inevitable impurities, and the impurity content is not higher than 0.01%.
3. The preparation method according to claim 1, characterized in that: The silanized calcite is prepared according to the following method: washing and drying the calcite, grinding it and passing it through a 80-100 mesh sieve to obtain calcite powder; The obtained calcite powder is placed in a silane coupling agent and ultrasonically treated at a power of 600 to 800 W for 30 to 50 minutes, then allowed to stand for 10 to 30 minutes, and then filtered, and the obtained precipitate is dried to obtain silanized calcite.
4. The preparation method according to claim 3, characterized in that: The silane coupling agent is selected from any one of vinyl triethoxy silane, vinyl trimethoxy silane and vinyl tri (β-methoxyethoxy) silane.
5. The preparation method according to claim 1, characterized in that: The ultrasonic treatment conditions are: power 300-600W, time 10-20min, and a working process of pausing for 1s every 10s of ultrasonic treatment.
6. The preparation method according to claim 1, characterized in that: The cationic monomer is at least one selected from diallyldimethylammonium chloride, acrylamidopropyltrimethylammonium chloride, methacrylamidopropyltrimethylammonium chloride, acryloyloxyethyltrimethylammonium chloride, methacryloyloxyethyltrimethylammonium chloride, and acryloyloxyethyltrimethylammonium chloride.
7. The preparation method according to claim 1, characterized in that: The nonionic monomer is selected from at least one of acrylamide, dimethylacrylamide, diethylacrylamide, hydroxyethylacrylamide, dimethylaminopropylacrylamide and dimethylaminopropylmethacrylamide.
8. The preparation method according to claim 1, characterized in that: The added amount of the aluminum-iron alloy-coated silanized calcite is 0.3-0.7 of the mass of the polyethylene glycol diacrylate.
9. The preparation method according to claim 1, characterized in that: The initiator is selected from any one of potassium persulfate, ammonium persulfate and sodium persulfate; The added amount of the initiator is 0.2-0.5% of the mass of the cationic monomer.
10. The preparation method according to claim 1, characterized in that: The cross-linking agent is selected from any one of catechol, hydroquinone and resorcinol; The added amount of the crosslinking agent is 0.1-0.3% of the mass of the cationic monomer.